Pemanfaatan Digital Marketing Dalam Proses Jaringan Bisnis Usaha Hotmie Roll - Resya Dwi Marselina; Chyntia Ika Pertiwi; Fitria Anjarsari; Nunik Nur Asiah Jamil; Siti Haniah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The purpose of this research is to find out how digital marketing is used in building business networks. This research uses descriptive qualitative research methods. The object of this research is the Hot MieRoll business. The results of this research are digital marketing that the HotMie Roll business can use as an effort to build a business network is creating a Google Business account, creating social media as a marketing medium and creating photo or video content which will later be uploaded on social media by following current trends.